Management of Periprosthetic Joint Infections After Hemiarthroplasty of the Hip: A Critical Analysis Review. Issue 9 (26th September 2022) - Bureau, Antoine; Bourget-Murray, Jonathan; Azad, Marisa A.; Abdelbary, Hesham; Grammatopoulos, George; Garceau, Simon P.
Abstract : ➢ Periprosthetic joint infection (PJI) following hip hemiarthroplasty (HA) is a devastating complication, incurring immense health-care costs associated with its treatment and placing considerable burden on patients and their families. These patients often require multiple surgical procedures, extended hospitalization, and prolonged antimicrobial therapy. ➢ Notable risk factors include older age, higher American Society of Anesthesiologists (ASA) score, inadequate antibiotic prophylaxis, non-antibiotic-loaded cementation of the femoral implant, longer duration of the surgical procedure, and postoperative drainage and hematoma. ➢ Although the most frequent infecting organisms are gram-positive cocci such as Staphylococcus aureus, there is a higher proportion of patients with gram-negative and polymicrobial infections after hip HA compared with patients who underwent total hip arthroplasty. ➢ Several surgical strategies exist. Regardless of the preferred surgical treatment, successful management of these infections requires a comprehensive surgical debridement focused on eradicating the biofilm followed by appropriate antibiotic therapy. ➢ A multidisciplinary approach led by surgeons familiar with PJI treatment and infectious disease specialists is recommended for all cases of PJI after hip HA to increase the likelihood of treatment success.